A scientometric analysis of international publication trends in oyster research - Azra, Mohamad Nor; Mohd Noor, Mohd Iqbal; Zekker, Ivar (Frontiers in Marine Science, 2022)
Oysters form extraordinary ecosystems (e.g. oyster reefs) with a high economic importance (e.g. aquaculture) to the world’s aquatic ecological systems. Shellfish, especially mollusks, have a significant contribution towards the future global food security. However, to the best of our knowledge, there are no bibliometric studies on oyster-related topics. In the present study, we queried the Web of Science Core Collection (WOSCC) database to selectively identify the scope of oyster publications. Citespace was used as a tool for the co-citation analysis and Microsoft Excel software for the handling of descriptive datasets. A total of 19,202 papers available from WOSCC between 1975 and 2021 were extracted and analyzed. Our data indicated that the number of publications increased two-fold between 2010 (654) and 2021 (1309). Our study also revealed that almost 70% of the publications were published by the five countries that lead oyster research in the world, USA, China, France, Australia, and Japan. Over the last five decades, there are a total of 7,905 participating institutions, a tremendous 40,939 authors involved, and 2,319 different journals published about oyster related studies. To the best of our knowledge, this is the first scientometric review to identify the scope of oyster research and publications. These findings show the emergence of oyster research and could attract various stakeholders, especially the early career researchers in various fields to collaborate in oyster research in the future.